Self-rated health status and illiteracy as death predictors in a Brazilian cohort. - Sayuri Inuzuka; Paulo Cesar Veiga Jardim; Shafika Abrahams-Gessel; Ludimila Garcia Souza; Ana Carolina Rezende; Naiana Borges Perillo; Samanta Garcia Souza; Ymara Cássia Luciana Araújo; Rogério Orlow Oliveira; Weimar Sebba Barroso; Andréa Cristina Sousa; Ana Luiza Lima Sousa; et al. (PLoS ONE)
Cohort studies assessing predictive values of self-rated health (SRH) and illiteracy on mortality in low-to-middle income countries are missing in the literature. Aiming to determine if these two variables were death predictors, an observational prospective population-based cohort study was conducted in a Brazilian small city. The cohort was established in 2002 with a representative sample of adults living in the city, and re-assessed in 2015. Sociodemographic (including illiteracy), anthropometric, lifestyle, previous CVD, and SRH data were collected. Cox proportional hazard models were designed to assess SRH and illiteracy in 2002 as death (all causes, CVD and non-CVD) predictors in 2015. From a total of 1066 individuals included in this study, 95(9%) died of non-CVD causes and 53(5%) from CVD causes. Mortality rates were higher among those with worse SRH in comparison to better health status categories for all causes of death, CVD and non-CVD deaths (p<0.001 for all outcomes). Similarly, illiterate individuals had higher mortality rates in comparison to non-illiterate for all causes of death (p<0.001), CVD (p = 0.004) and non-CVD death (p<0.001). Higher SRH negatively predicted CVD death (HR 0.44; 95%CI 0.44-0.95; p = 0.027) and all causes of death (OR 0.40; 95%CI 0.20-0.78; p = 0.008) while illiteracy positively predicted Non-CVD death (OR 1.59; 95%CI 1.03-2.54; p = 0.046). In conclusion, we found in this large Brazilian cohort followed for 13 years that better health perception was a negative predictor of death from all causes and CVD deaths, while illiteracy was a positive predictor of non-CVD deaths.